Peningkatan Ketrampilan Implementasi Ilmu Fiqih Kawula Muda Melalui Pelatihan Perawatan Jenazah - Hidayat, Rohmat; Shobirin, Mochammad Syafiuddin; Mutrofin, Akmam; Nurrochmah, Mauliyah; Syafiyah, Nihayatus; Marwa, Ilmi Fadhilah; Zakiyuddin, Mohammad (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2023)
Fiqh, the jurisprudential science, plays a significant role in Islam by governing various aspects of daily life, including the procedures for handling deceased bodies. However, understanding of fiqh and its application in the context of funeral rites, especially among the younger generation, is often limited. This community engagement program aims to enhance the understanding and skills of young individuals in fiqh, specifically in relation to the proper handling of deceased bodies. The program responds to the needs of the community in Murukan Village, Mojoagung Subdistrict, Jombang Regency, in improving their comprehension of fiqh and its application in funeral rites according to Islamic teachings. A sound understanding of fiqh allows individuals to perform religious rituals, navigate social life, and maintain moral ethics in accordance with religious principles. This community engagement program employs the Participatory Action Research (PAR) method, which is oriented towards empowering the community. The method focuses on active participation from community members or individuals involved in the research. The procedural stages of this engagement are divided into several activities, including Needs Identification, Training Material Development, Training Implementation, and Evaluation. In the context of funeral rites, this understanding enables the proper execution of tasks in line with religious values. The program involves collaboration with the village government, youth organizations, and religious institutions to support the execution of funeral training. Overall, this program successfully addresses the community's needs, improves understanding and skills related to funeral rites in accordance with Islamic teachings, and promotes active participation of the younger generation in preserving Islamic traditions and values.